Impoving the effectiveness of learning military concepts based on interactive methods - Xurramov Mansur (Research Parks Publishing LLC, 2020)
From the first years of independence of the Republic of Uzbekistan, special attention has been paid to the improvement of education, in particular, military education. During a historically short period of time, great work has been done in this area in our country, and it continues to this day. The introduction of interactive teaching methods in the education system is one of the important factors in the training of modern personnel. Today, it is not enough for a teacher to have in-depth knowledge in their field and to impart a large amount of knowledge to an audience full of knowledge-hungry young people. Numerous studies have shown that a new approach to teaching and the use of proactive approaches in teaching students is one of the most effective ways of teaching. Simply put, students can easily understand, comprehend, and remember the material provided only when they are actively involved in the learning process. Therefore, today's major methodological innovations require the use of interactive teaching methods. The purpose of creating these teaching recommendations is to reveal the specifics of some interactive teaching methods, to highlight the technologies of correct application of these methods in the classroom. The work of leading teachers of our country and abroad in this area was widely used in the preparation of teaching recommendations. I hope that these recommendations will help teachers of educational institutions to use interactive methods in teaching. This article shows the effectiveness of interactive methods